Strategi Dinas Tenaga Kerja dalam Meningkatkan Penempatan Tenaga Kerja dan Perluasan Kesempatan Kerja di Kabupaten Sidoarjo - Siska Zunita Anggraini; Tukiman Tukiman (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Unemployment is the biggest problem faced by every country, both at the provincial and district/city levels. Sidoarjo Regency is the area with the highest open unemployment rate in East Java. The unemployment rate is a problem that must be quickly addressed by the Sidoarjo Regency government through the Manpower Service which plays an important role in terms of employment in order to achieve people's welfare. In this case, the local government is trying to suppress the increasing unemployment rate. One of them is the strategy of manpower placement and expansion of job opportunities through the Job Fair/JobFair program. This study aims to determine the strategy of the Department of Manpower in increasing the placement of workers and expanding job opportunities in Sidoarjo Regency. The type of this research is using descriptive qualitative with data collection techniques in the form of interviews, observations, documentation and literature study. The focus of this research is to use 3 (three) indicators of strategic management, namely: Strategy Formulation, Strategy Implementation and Strategy Evaluation. Sources of data used are informants and documents related to research. Sampling in this research is using purposive sampling technique. Data analysis techniques used are data collection, data condensation, data presentation and drawing conclusions. The results of this study indicate that the Department of Manpower's strategy in increasing manpower placement and expanding job opportunities is through the Open Job Fair/JobFair program which is carried out online and offline which is located in the Sidoarjo District Square. The implementation of the program is quite good, it's just that there are job seekers who are not ready with online JobFair registration, and there are also job seekers who choose jobs that are not in accordance with their fields. The evaluation carried out was good, namely by recording job seekers who managed to get a job.